Iron and Non-Iron-Related Characteristics of Multiple Sclerosis and Neuromyelitis Optica Lesions at 7T MRI - Chawla, S; Kister, I; Wuerfel, J; Brisset, J-C; Liu, S; Sinnecker, T; Dusek, P; Haacke, E M; Paul, F; Ge, Y (American journal of neuroradiology, 2016)
BACKGROUND AND PURPOSE: Characterization of iron deposition associated with demyelinating lesions of multiple sclerosis and neuromyelitis optica has not been well studied. Our aim was to investigate the potential of ultra-high-field MR imaging to distinguish MS from neuromyelitis optica and to characterize tissue injury associated with iron pathology within lesions. MATERIALS AND METHODS: Twenty-one patients with MS and 21 patients with neuromyelitis optica underwent 7T high-resolution 2D-gradient-echo-T2* and 3D-susceptibility-weighted imaging. An in-house-developed algorithm was used to reconstruct quantitative susceptibility mapping from SWI. Lesions were classified as "iron-laden" if they demonstrated hypointensity on gradient-echo-T2*-weighted images and/or SWI and hyperintensity on quantitative susceptibility mapping. Lesions were considered "non-iron-laden" if they were hyperintense on gradient-echo-T2* and isointense or hyperintense on quantitative susceptibility mapping. RESULTS: Of 21 patients with MS, 19 (90.5%) demonstrated at least 1 quantitative susceptibility mapping-hyperintense lesion, and 11/21 (52.4%) had iron-laden lesions. No quantitative susceptibility mapping-hyperintense or iron-laden lesions were observed in any patients with neuromyelitis optica. Iron-laden and non-iron-laden lesions could each be further characterized into 2 distinct patterns based on lesion signal and morphology on gradient-echo-T2*/SWI and quantitative susceptibility mapping. In MS, most lesions (n = 262, 75.9% of all lesions) were hyperintense on gradient-echo T2* and isointense on quantitative susceptibility mapping (pattern A), while a small minority (n = 26, 7.5% of all lesions) were hyperintense on both gradient-echo-T2* and quantitative susceptibility mapping (pattern B). Iron-laden lesions (n = 57, 16.5% of all lesions) were further classified as nodular (n = 22, 6.4%, pattern C) or ringlike (n = 35, 10.1%, pattern D). CONCLUSIONS: Ultra-high-field MR imaging may be useful in distinguishing MS from neuromyelitis optica. Different patterns related to iron and noniron pathology may provide in vivo insight into the pathophysiology of lesions in MS.
Keywords: Iron; lidé; mladiství; magnetická rezonanční tomografie; Adult; Brain Mapping; Middle Aged; počítačové zpracování obrazu; železo; elektromagnetická pole; Magnetic Resonance Imaging; Multiple Sclerosis; Infant; Female; neuromyelitis optica; dítě; Image Processing, Computer-Assisted; Adolescent; Humans; Infant, Newborn; algoritmy; roztroušená skleróza; předškolní dítě; lidé středního věku; Algorithms; Child, Preschool; mužské pohlaví; mladý dospělý; Electromagnetic Fields; novorozenec; ženské pohlaví; Young Adult; zobrazování trojrozměrné; mapování mozku; Imaging, Three-Dimensional; Male; Neuromyelitis Optica; Child; dospělí; kojenec